Neutral sphingomyelinase 2 inhibitors based on the pyrazolo[1,5-a]pyrimidin-3-amine scaffold - Novotna, Katerina; Thomas, Ajit G; Stepanek, Ondrej; Murphy, Brennan; Hin, Niyada; Skacel, Jan; Mueller, Louis; Tenora, Lukas; Pal, Arindom; Alt, Jesse; Wu, Ying; Paule, James; et al. (European journal of medicinal chemistry, 2023)
Neutral sphingomyelinase 2 (nSMase2) has gained increasing attention as a therapeutic target to regulate ceramide production in various disease conditions. Phenyl (R)-(1-(3-(3,4-dimethoxyphenyl)-2,6-dimethylimidazo[1,2-b]pyridazin-8-yl)-pyrrolidin-3-yl)carbamate (PDDC) is a submicromolar nSMase2 inhibitor and has been widely used to study the pharmacological effects of nSMase2 inhibition. Through screening of compounds containing a bicyclic 5-6 fused ring, larotrectinib containing a pyrazolo[1,5-a]pyrimidine ring was identified as a low micromolar inhibitor of nSMase2. This prompted us to investigate the pyrazolo[1,5-a]pyrimidin-3-amine ring as a novel scaffold to replace the imidazo[1,2-b]pyridazine-8-amine ring of PDDC. A series of molecules containing a pyrazolo[1,5-a]pyrimidin-3-amine ring were synthesized and tested for their ability to inhibit human nSMase2. Several compounds exhibited nSMase2 inhibitory potency superior to that of PDDC. Among these, N,N-dimethyl-5-morpholinopyrazolo[1,5-a]pyrimidin-3-amine (11j) was found to be metabolically stable in liver microsomes and orally available with a favorable brain-to-plasma ratio, demonstrating the potential of pyrazolo[1,5-a]pyrimidine ring as an effective scaffold for nSMase2 inhibition.
Keywords: Ceramide; Neutral sphingomyelinase 2; Sphingomyelin Phosphodiesterase; Ceramides; Pyrazolo[1,5-a]pyrimidin-3-amine; aminy; Humans; Pyrimidines; sfingomyelinfosfodiesterasa; ceramidy; Sphingomyelin; pyrimidiny; Phosphodiesterase; lidé; Amines